1980
DOI: 10.1111/j.1365-2621.1980.tb02599.x
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem Invasion of Muscle Food by a Proteolytic Bacterium

Abstract: Serratia marcescens was used to study the process of bacterial invasion of intact and cornminuted meats (fresh and frozen-thawed) as well as the bacterium's ability to hydrolyze reconstituted collagen. Fresh intact pork was more susceptible to invasion when the inoculated surface was vertical to the inoculum. In cornminuted beef and pork, invasion was more extensive in meat that had undergone at least one freeze-thaw cycle. The addition of sodium tripolyphosphate (up to 0.5% , w/w) to cornminuted beef and pork… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 12 publications
0
12
1
Order By: Relevance
“…Such surface contaminations may increase after slaughtering because biological mechanisms preventing contaminations have ceased to function, and protective coverings have been removed (Elmossalami & Wassef, 1971). Some later studies though demonstrated that microorganisms appeared to be able to penetrate muscle tissue, and authors attributed this to a wide range of different mechanisms (Anderson, Marshall, & Dickson, 1991;Elmossalami & Wassef, 1971;Gill, Leet, & Penney, 1984;Gill & Penney, 1977;Gill & Penney, 1982;Gill, Uttaro, Badoni, & Zawadski, 2008;Gupta & Nagamohini, 1992;Sikes & Maxcy, 1980;Thomas, O'Rourke, & McMeekin, 1987;Warsow, Orta-Ramirez, Marks, Ryser, & Booren, 2008).…”
Section: Introductionmentioning
confidence: 91%
“…Such surface contaminations may increase after slaughtering because biological mechanisms preventing contaminations have ceased to function, and protective coverings have been removed (Elmossalami & Wassef, 1971). Some later studies though demonstrated that microorganisms appeared to be able to penetrate muscle tissue, and authors attributed this to a wide range of different mechanisms (Anderson, Marshall, & Dickson, 1991;Elmossalami & Wassef, 1971;Gill, Leet, & Penney, 1984;Gill & Penney, 1977;Gill & Penney, 1982;Gill, Uttaro, Badoni, & Zawadski, 2008;Gupta & Nagamohini, 1992;Sikes & Maxcy, 1980;Thomas, O'Rourke, & McMeekin, 1987;Warsow, Orta-Ramirez, Marks, Ryser, & Booren, 2008).…”
Section: Introductionmentioning
confidence: 91%
“…The results are thought to be a consequence of increased interstitial cavity sizes between cells caused by the formation of ice crystal artifacts [8]. By comparison another study found no increased bacterial invasion after freezing [9].…”
Section: Introductionmentioning
confidence: 95%
“…Bacterial invasion after a freeze-thaw cycle has also been investigated, freezing led to more extensive bacterial proliferation in SMT in comparison to fresh SMT samples [8]. The results are thought to be a consequence of increased interstitial cavity sizes between cells caused by the formation of ice crystal artifacts [8].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations